A case-control study on food frequency and meal pattern distribution in coronary artery disease patients attending tertiary care teaching hospitals - Siddharth Bhagvandas Agrawal; Dishant Bhavin Upadhyay; Aparajita Abhinava Shukla (Wolters Kluwer Medknow Publications, 2020)
Context: Coronary artery disease (CAD) is the blockage of coronary arteries, usually consequent to atherosclerosis. CAD is a lifestyle disease with an increasing disease burden in society. Evaluation of risk factors for CAD is crucial for its prevention. Lifestyle components like calorie consumption chronology, saturated fatty acid (SAFA) intake, reclining time, nocturnal eating and intermittent fasting were considered. Aims: To correlate calorie distribution, SAFA intake, reclining time, nocturnal eating and intermittent fasting with occurrence of CAD. Study Design/Materials and Methods: A case-control study consisting of 235 cases and 185 controls. Questionnaire was self-designed according to NIN guidelines. Study was ICMR funded and data analysis was done using Microsoft Excel and IBM SPSS. Results: Across case and control groups, total calorie consumption difference was insignificant (P = 0.42). Calories consumed in breakfast slot (P = 0.001) and dinner slot (P = 0.003) were significantly different possibly due to discrepancy among circadian variation in insulin sensitivity and calorie consumption distribution. Reclining time <1 h in afternoon (odds ratio [OR] = 2.24, 95%, 1.481-3.356) and night (OR = 2.05, 95% confidence limit [CL], 1.233-3.410), SAFA consumption (OR = 2.006, 95% CL, 1.214-3.316), intermittent fasting (OR = 1.748, 95% CL, 0.997-3.067) and nocturnal eating (OR = 1.291, 95% CL, 0.779--2.141) are potential risk factors. Conclusions: Calorie consumption chronology, SAFA intake, Reclining time, Nocturnal eating and intermittent fasting emerged as significant risk factors.